Վենետիկի և Ջենովայի հակամարտությունը. 1294 թ. Այասի ծովամարտը - Զոհրաբ Գևորգյան (ՀՀ ԳԱԱ հրատ.)
Средиземноморское побережье Киликийской Армении стало ареной второй войны (1294–1299) между республиками Венеции и Генуи. Айас стал центром соперничества итальянских республик. Доказательства этого есть в источнике, связанном с тамплиерами,– «Деяния киприотов» – где говорится, что в 1293 году венецианские галеры прибыли в Айас и там конфисковали генуэзское торговое судно. The Mediterranean coast of Cilician Armenia became the arena of the second war (1294–1299) between the Republics of Venice and Genoa. Ayas became the center of rivalry of Italian republics. We can find evidences in the source concerned with Templars in “The Deeds of Cypriots”, where we can read that in 1293 Venetian galleys arrived at Ayas and there confiscated a Genoese merchant ship. Eventually, at the seashore of Ayas between Venetian and Genoese fleet took place a sea battle, which had so big fame in the medieval world that anonymous Genoese poet of the same period wrote a poem dedicated to this battle.
Keywords: History; Medieval History; D History